PENATAAN KELEMBAGAAN BADAN PERMUSYAWARATAN DESA BERDASARKAN UU NOMOR 6 TAHUN 2014 - Maulidiah, Sri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
Historically, the existence of villages in Indonesia have existed long before the Unitary Republic of Indonesia (NKRI) exist or are formed. As evidence of the existence of the village, can be seen from the explanation of Article 18 of the Constitution of the Republic of Indonesia Year 1945, where there are approximately 250 "Zelfbesturende landschappen", such as the Village in Java and Bali, Nagari in Minangkabau, Dusun and Marga in Palembang, and other etc. The village is a unified society based on customary law and customary law are settled within a certain region demarcated; has a spiritual and physical bond is very strong, both as an element of collateral as well as have the same political, economic, social and security and so forth; has selected board members together, have a certain amount of wealth and the right to conduct his own household. " The village administration is composed of the village authorities and Village Consultative Body (formerly Village Parliament) or abbreviated with BPD, called elements of village administration. As one element of BPD village administration certainly has a very important role in promoting and developing the village. Therefore, BPD certainly need institutional arrangement to BPD in accordance with legislation, in this case is Law No. 6 of 2014 concerning the village.